Oncogenic Truncations of ASXL1 Enhance a Motif for BRD4 ET-Domain Binding. Issue 22 (5th November 2021) - Burgess, Abigail E.; Kleffmann, Torsten; Mace, Peter D.
Graphical abstract: Highlights: Mechanism underlying gain-of-function interactions between ASXL1 and BRD4. ET-binding motif of ASXL1 varies slightly from canonical motifs, but binds with high affinity. ASXL-ET-domain binding is conserved across BET domain proteins and ASXL orthologs. ASXL1-ET-domain binding in cells is enhanced in the context of truncated ASXL1 variants relative to wild-type ASXL1. Abstract: Proper regulation of gene-expression relies on specific protein–protein interactions between a myriad of epigenetic regulators. As such, mutation of genes encoding epigenetic regulators often drive cancer and developmental disorders. Additional sex combs-like protein 1 (ASXL1) is a key example, where mutations frequently drive haematological cancers and can cause developmental disorders. It has been reported that nonsense mutations in ASXL1 promote an interaction with BRD4, another central epigenetic regulator. Here we provide a molecular mechanism for the BRD4-ASXL1 interaction, demonstrating that a motif near to common truncation breakpoints of ASXL1 contains an epitope that binds the ET domain within BRD4. Binding-studies show that this interaction is analogous to common ET-binding modes of BRD4-interactors, and that all three ASX-like protein orthologs (ASXL1–3) contain a functional ET domain-binding epitope. Crucially, we observe that BRD4-ASXL1 binding is markedly increased in the prevalent ASXL1 Y591X truncation that maintains the BRD4-binding epitope, relative to full-length ASXL1 or truncated proteins that delete the epitope. Together, these results show that ASXL1 truncation enhances BRD4 recruitment to transcriptional complexes via its ET domain, which could misdirect regulatory activity of either BRD4 or ASXL1 and may inform potential therapeutic interventions.